2020
DOI: 10.1038/s41598-020-58498-2
|View full text |Cite
|
Sign up to set email alerts
|

Weighing the role of skeletal muscle mass and muscle density in cancer patients receiving PD-1/PD-L1 checkpoint inhibitors: a multicenter real-life study

Abstract: Sarcopenia represents one of the hallmarks of all chronic diseases, including cancer, and was already investigated as a prognostic marker in the pre-immunotherapy era. Sarcopenia can be evaluated using cross-sectional image analysis of CT-scans, at the level of the third lumbar vertebra (L3), to estimate the skeletal muscle index (SMI), a surrogate of skeletal muscle mass, and to evaluate the skeletal muscle density (SMD). We performed a retrospective analysis of consecutive advanced cancer patient treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
89
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(99 citation statements)
references
References 37 publications
7
89
2
1
Order By: Relevance
“…Assessment tools included the cross‐sectional area of the psoas or lumbar muscles divided by body height squared. However, three of these studies did not assess the effects of PD‐L1 expressions on outcomes 14–16 . Only one study adjusted for the predictive impact of muscle quantity by PD‐L1 expression and reported the absence of an association with PFS, 17 which is consistent with our study, although the assessment tool used for muscle quantity was different.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Assessment tools included the cross‐sectional area of the psoas or lumbar muscles divided by body height squared. However, three of these studies did not assess the effects of PD‐L1 expressions on outcomes 14–16 . Only one study adjusted for the predictive impact of muscle quantity by PD‐L1 expression and reported the absence of an association with PFS, 17 which is consistent with our study, although the assessment tool used for muscle quantity was different.…”
Section: Discussionsupporting
confidence: 84%
“…While a previous study stated that decreased lumbar muscle density is predictive of inferior PFS in patients with metastatic melanoma treated with ipilimumab, 25 several other studies conducted in patients with metastatic NSCLC treated with PD‐1/PD‐L1 inhibitors were skeptical about its predictive value 10,17 . Cortellini et al retrospectively reviewed the impact of muscle quality on PFS in association with PD‐1/PD‐L1 inhibitor use in a mixed cancer population comprising 46 patients with advanced NSCLC and 54 patients with other advanced cancers including renal cell carcinoma and melanoma 14 . They measured lumbar skeletal muscle density as an indicator of muscle quality and showed no association between muscle quality and PFS or ORR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The predictive value of nutritional status for ICI efficacy is not well-established, which is in contrast with the plethora of data supporting the association between malnutrition and overall survival. [21][22][23] Only one recent study reported that patients with non-small cell lung cancer (NSCLC) with a PNI ≤45.5 had significantly worse ORR, DCR and PFS as compared with patients with PNI >45.5. 24 Yet, there are several reasons that poor nutritional status could impair ICI effectiveness.…”
mentioning
confidence: 99%